1981
DOI: 10.1002/1097-4679(198107)37:3<484::aid-jclp2270370306>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different aspects of self-concept for young, middle-aged, and older women

Abstract: Previous research that focused on self-esteem in adult women has yielded a variety of contradictory results, with some studias that report more positive self-concepts in the middle-aged in comparison to older and younger women and others that report the o osite. Similar conflicting findings have been presented for women over 60. !&s study com ared women in four age groups: 18 to 22,29 t o 39,40 t o 55, and 60 to 75 on tfe Tennessee Self Concept Scale, which yields self-esteem score9 on different life aspects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Several cross-sectional studies showed that middle-aged adults had higher self-esteem than did older adults (Jaquish & Ripple, 1981;Ranzjin, Keeves, Luszcz, & Feather, 1998;Tiggemann & Lynch, 2001;Ward, 1977). In contrast, Gove et al (1989) found that their oldest cohort (age 75 and older) had the highest level of self-esteem, and several studies have failed to show any significant age differences (Erdwins, Mellinger, & Tyer, 1981;Ryff, 1989;Trimakas & Nicholay, 1974). Only two longitudinal studies have examined self-esteem in old age; one reported no change over a 2-year period for individuals aged 58 years to 64 years (Reitzes, Mutran, & Fernandez, 1996), and the other reported a decline from age 65 years to age 75 years (Coleman, Ivani-Chalian, & Robinson, 1993).…”
Section: Previous Research On Self-esteem Developmentmentioning
confidence: 99%
“…Several cross-sectional studies showed that middle-aged adults had higher self-esteem than did older adults (Jaquish & Ripple, 1981;Ranzjin, Keeves, Luszcz, & Feather, 1998;Tiggemann & Lynch, 2001;Ward, 1977). In contrast, Gove et al (1989) found that their oldest cohort (age 75 and older) had the highest level of self-esteem, and several studies have failed to show any significant age differences (Erdwins, Mellinger, & Tyer, 1981;Ryff, 1989;Trimakas & Nicholay, 1974). Only two longitudinal studies have examined self-esteem in old age; one reported no change over a 2-year period for individuals aged 58 years to 64 years (Reitzes, Mutran, & Fernandez, 1996), and the other reported a decline from age 65 years to age 75 years (Coleman, Ivani-Chalian, & Robinson, 1993).…”
Section: Previous Research On Self-esteem Developmentmentioning
confidence: 99%
“…In contrast, Gove et al (1989) found the highest levels of self-esteem in the oldest cohort (age 75 years and older). Moreover, several studies have failed to find significant age differences, including Trimakas and Nicolay's (1974) study of individuals age 66 -88 years, Erdwins et al (1981) study of four cohorts ranging in age from 18 to 75 years, and Ryff's (1989) study comparing middleaged adults (mean age ϭ 50 years) and older adults (mean age ϭ 75 years). Reflecting the lack of consistency in previous findings, researchers reviewing the literature on self-esteem and aging have failed to reach consensus on whether self-esteem increases, decreases, or remains stable in old age (Bengtson, Reedy, & Gordon, 1985;Brandtstaedter & Greve, 1994;Demo, 1992).…”
Section: Old Agementioning
confidence: 99%
“…In contrast, Gove et al (1989) found the highest levels of self-esteem in the oldest cohort (age 75 years and older). Moreover, several studies have failed to find significant age differences, including Trimakas and Nicolay's (1974) study of individuals age 66 -88 years, Erdwins et al (1981) study of four cohorts ranging in age from 18 to 75 years, and Ryff's (1989) study comparing middleaged adults (mean age ϭ 50 years) and older adults (mean age ϭ 75 years). Reflecting the lack of consistency in previous findings, researchers reviewing the literature on self-esteem and aging have failed to reach consensus on whether self-esteem increases, decreases, or remains stable in old age (Bengtson, Reedy, & Gordon, 1985;Brandtstaedter & Greve, 1994;Demo, 1992).…”
Section: Old Agementioning
confidence: 99%